Marching to the Beat of Their Own Drum: How Beta-Israel Uses Liturgical Music to Maintain its Roots Within a Foreign Culture - Dicker, Yehuda (Iggrot Ha’Ari, 2023)
Known as Falasha, Ethiopian Jews lived in isolation for centuries practicing an ancient, pre-talmudic form of Judaism, which traces its origins back to Solomon and Sheba.” It was not until 1984 that this Falasha community, known as Beta-Israel, was covertly airlifted from Sudan during the civil war and brought to the State of Israel. Their arrival was accompanied by quite the culture shock for a variety of reasons, a significant one being religion. Much of the community quickly assimilated into modern society, leaving behind their traditional religious Ethiopian roots. As a result, the Beta-Israel community became a minority, a waning religious sect of Judaism in Israel. Yet, those who maintained their roots continued their practices with full vigor. Included in these practices is their unique liturgy, liturgical music and use of musical instruments in prayer. This paper will examine texts which discuss Ethiopian liturgical music in depth and explore what role this music plays in preserving their community.